2009
DOI: 10.1002/ppap.200931111
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Improvement of Polyimide/Metal Interface by He/O2/NF3 Atmospheric Pressure Plasma

Abstract: The surface of polyimide (PI) was modified with He/O2/NF3 dielectric barrier discharge generated by 13.56 MHz r.f. at atmospheric pressure in order to improve adhesion between metal (Cu/Cr) and PI. He/O2/NF3 plasma severely etched the surface of PI and formed many conical clusters of below 100 nm diameter on the PI surface. The surface roughness of PI was increased from 0.4 to 11 nm with r.f. power. X‐ray photoelectron spectroscopy (XPS) analysis showed that oxygen concentration was increased as much as the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…There are many studies on the effects of atmospheric plasma surface treatment on the adhesion of certain types of dental material, primarily for polymers 18 19 20 30 32 33 34 and less so for zirconia 24 31 and titanium. 14 22 31 Some authors have reported that plasma surface modification procedures allow the formation of stronger bonds, improve wettability, and produce chemically active sites for the adhesion of other molecules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many studies on the effects of atmospheric plasma surface treatment on the adhesion of certain types of dental material, primarily for polymers 18 19 20 30 32 33 34 and less so for zirconia 24 31 and titanium. 14 22 31 Some authors have reported that plasma surface modification procedures allow the formation of stronger bonds, improve wettability, and produce chemically active sites for the adhesion of other molecules.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to effects caused by the time of treatment, the range of applied power, the waveforms of the applied voltage or the distance between the sample surface and the plasma applicator nozzle, as noted by many publications. 20 21 31 33…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-pressure plasma surface treatments have been successfully employed in order to increase the wettability and absorbability of polymer lms or to improve the adhesion of polymer/metal joins. [5][6][7][8] In most of the existing studies, however, the focus has been on the plasma treatment of the polymer, and little is known about the inuence of plasma-treating the alloycoated metal surfaces. [9][10][11][12] In one of the few existing studies, Pohl et al investigated the inuence of both reducing and oxidizing low-pressure plasmas on ZnMgAl coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Esto pone de manifiesto la efectividad del tratamiento de plasma atmosférico respecto a la mejora de la adhesión, en cualquiera de las condiciones estudiadas. (H. M Hyeop et al 2007, M. R. Sanchis et al 2007, Okubo Masaaki et al 2008, Bin Lee S et al 2009, Gao Zhiqiang et al 2009,. C. E. Nwankire and D. P. Dowling 2010, V. Fombuena-Borras et al 2012, O. G. Armagan et al 2013, K. Navaneetha Pandiyaraj et al 2013, O. G. Armagan et al 2014) Hay que tener en cuenta los mejores resultados con la utilización de atmósfera de nitrógeno.…”
unclassified